2003
DOI: 10.2214/ajr.180.3.1800827
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cystic Lung Disease: Diagnostic Accuracy of High-Resolution CT in 92 Patients

Abstract: Although various chronic cystic lung diseases often have a characteristic appearance that allows their distinction on high-resolution CT, considerable overlap exists among the CT findings. Therefore, lung biopsy is often required for a definitive diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 30 publications
2
64
0
Order By: Relevance
“…The combination of cysts and nodules, which spare the lung bases, in a male smoker, is sufficient for a confident diagnosis of LHC. (120) In women smokers, lymphangioleiomyomatosis (LAM) should be considered, since nodules (and cysts) can also be present. (121) Langerhans cells can be identified in BAL fluid, although the sensitivity and specificity of this test are quite low.…”
Section: Langerhans Cell Histiocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of cysts and nodules, which spare the lung bases, in a male smoker, is sufficient for a confident diagnosis of LHC. (120) In women smokers, lymphangioleiomyomatosis (LAM) should be considered, since nodules (and cysts) can also be present. (121) Langerhans cells can be identified in BAL fluid, although the sensitivity and specificity of this test are quite low.…”
Section: Langerhans Cell Histiocytosismentioning
confidence: 99%
“…(123) Other interstitial lung diseases with cysts Cysts can occur in several DILDs, including chronic HP, chronic sarcoidosis, lymphoid interstitial pneumonia, DIP, and RB-ILD. (120,124,125) In a study of the diagnostic accuracy of HRCT in chronic cystic lung diseases, (120) a reliable diagnosis was rendered by two radiologists in approximately half of the cases. (126) In that study, the diagnosis was correct in approximately 90% of cases in which DIP/RB-ILD, lymphoid interstitial pneumonia, LAM, and LCH were the diagnoses, and in 100% of cases in which UIP was the diagnosis.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…HRCT imaging has the greatest diagnostic value and is necessary to perform for confirmation of diagnosis. In a previous study, the diagnostic accuracy of LAM was found to be 72% by CT alone (14). The diagnosis of LAM requires a HRCT scan that demonstrates diffuse, round or ovoid, thin-walled cysts, which vary in size between a few millimeters and 3 cm, and are surrounded by normal pulmonary parenchyma, while in advanced stages of the disease, total replacement of the lung tissue may be observed (5).…”
Section: Discussionmentioning
confidence: 99%
“…Cystic lung disease in BHD syndrome needs to be distinguished from other lung diseases that are characterized by multifocal or diffuse cystic changes, including lymphangioleiomyomatosis, pulmonary Langerhans cell histiocytosis, lymphocytic interstitial pneumonitis and emphysema [9][10][11]. [12].…”
Section: Coronal and Axial Ct Images Of Patient 2 Show Multiple Bilmentioning
confidence: 99%